DISFUNGSI TIROID, ANTIBODI PEROKSIDASE DAN HORMON PERANGSANGNYA - Stefanus Lembar; Benny Hartono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Hypothyroid in the pregnancy particularly in first trimester can influence the development of brain and neurophysiologic system infoetus. The diagnose approach of hypothyroid with laboratory evaluation which measure AntiTPO, TSH, and FT4 is the recommendedchoice. Full attention should be paid towards the treatment and management of hypothyroid in the pregnancy in order to avoid anybad complication.